AN ANALYSIS OF TYPES AND CATEGORIES CULTURE REPRESENTATION IN INDONESIAN ENGLISH TEXTBOOKS FOR JUNIOR HIGH SCHOOL - Azziyadi Azziyadi (International Journal of Educational Best Practices, 2026)
Most educators in Indonesia are insufficiently aware of the importance of fostering cultural awareness among students. This problem stems from the cultural context presented in the textbooks used in classroom teaching and learning, especially in the context of English. This study seeks to explore cultural representations and analyze the cultural content presented in Indonesian textbooks designed for senior high school students studying EFL. Using a descriptive qualitative methodology with a cross-cultural perspective, this research examines the cultural content and themes in three e-English teaching textbooks: English When English Rings Bell VII, English When English Rings Bell VII, and English Think Globally Act Locally IX, revised edition (2017), by Kemdikbud RI. Textbook analysis was guided by the cultural framework introduced by Cortazzi and Jin (1999), which specifically focuses on Target Culture, Source Culture, and International Culture. This textbook was chosen because it is commonly adopted in Indonesian junior high schools and officially published by the Indonesian Ministry of Education and Culture. The results of this research indicate a significant amount of content from the source culture, while the presence of the target culture and international culture remains quite limited. Additionally, among the 19 cultural elements classified under Big Culture and Small Culture, topics related to Small Culture were the most frequently featured. These outcomes draw attention to existing inequalities and underscore the importance of adopting a more inclusive and well-rounded approach to cultural instruction in English language education. By identifying these imbalances and broadening the range of cultural representations, teachers can better equip students with cross-cultural skills and nurture a deeper appreciation of diverse worldviews.